Exploring potential roles of long non-coding RNAs in cancer immunotherapy: a comprehensive review - Arshi, Asghar; Mahmoudi, Esmaeil; Raeisi, Farzaneh; Dehghan Tezerjani, Masoud; Bahramian, Elham; Ahmed, Yeasin; Peng, Chun (Frontiers in Immunology, 2024)
Cancer treatment has long been fraught with challenges, including drug resistance, metastasis, and recurrence, making it one of the most difficult diseases to treat effectively. Traditional therapeutic approaches often fall short due to their inability to target cancer stem cells and the complex genetic and epigenetic landscape of tumors. In recent years, cancer immunotherapy has revolutionized the field, offering new hope and viable alternatives to conventional treatments. A particularly promising area of research focuses on non-coding RNAs (ncRNAs), especially long non-coding RNAs (lncRNAs), and their role in cancer resistance and the modulation of signaling pathways.To address these challenges, we performed a comprehensive review of recent studies on lncRNAs and their impact on cancer immunotherapy. Our review highlights the crucial roles that lncRNAs play in affecting both innate and adaptive immunity, thereby influencing the outcomes of cancer treatments. Key observations from our review indicate that lncRNAs can modify the tumor immune microenvironment, enhance immune cell infiltration, and regulate cytokine production, all of which contribute to tumor growth and resistance to therapies. These insights suggest that lncRNAs could serve as potential targets for precision medicine, opening up new avenues for developing more effective cancer immunotherapies. By compiling recent research on lncRNAs across various cancers, this review aims to shed light on their mechanisms within the tumor immune microenvironment.